Fast and efficient removal of As(III) from water by CuFe2O4 with peroxymonosulfate: Effects of oxidation and adsorption. (1st March 2019) - Wei, Yuanfeng; Liu, Hui; Liu, Chengbin; Luo, Shenglian; Liu, Yutang; Yu, Xingwen; Ma, Jianhong; Yin, Kai; Feng, Haopeng
Abstract: Although oxidation of As(III) to As(V) is deemed necessary to promote arsenic removal, the oxidation process usually involves toxic byproducts, well-defined conditions, energy input or sludge generation. Moreover, extra operations are required to remove the resulting As(V). A heterogeneous catalytic process of CuFe2 O4 with peroxymonosulfate (PMS) is established for As(III) oxidation and adsorption. The PMS can be activated by CuFe2 O4 to generate radical species for As(III) oxidation. The CuFe2 O4 /PMS has a stronger affinity for arsenic than CuFe2 O4 alone. Oxidation and adsorption promote each other. As a result, the heterogeneous catalytic process is more efficient for As(III) removal than a preoxidation of As(III) followed by adsorption. The adsorption capacity for As on CuFe2 O4 /PMS reached up to 63.9 mg/g, which is much higher than that of As(III) (36.9 mg/g) or As(V) (45.4 mg/g) on CuFe2 O4 alone. The process can work effectively over a wide range of pH values (3–9) and temperatures (10–40 °C). Coexisting ions such as sulfate, carbonate, silicate and humic acid have an insignificant effect on As(III) removal. The As(III) (1415 μg/L) can be completely oxidized to As(V) and rapidly removed to below 10 μg/L (less than 15 min) using CuFe2 O4 (0.2 g/L)/PMS(100 μM). Moreover, the As(III) (50 μg/L) can be completely oxidized and removed within 1 min. The proposed process is easily applicable for the remediation of As(III)-contaminated water under ambient conditions. Graphical abstract: Highlights: Powerful radical generation on CuFe2 O4 induced by PMS. Enhanced adsorption capacity for As(III) on CuFe2 O4 /PMS than CuFe2 O4 . Operation across a broad range of geochemical conditions. Negligible influence of coexisting substances on As(III) removal. As(III) (1415 μg/L) could be lowered below 10 μg/L within 15 min.